Normocalcemia and Normal Thyroid Function in a Severe Vitamin D–Deficient Population - Omid Yazdani; Mohammad Reza Haeri; Reyhaneh Niayesh-Mehr (Advanced Biomedical Research)
Background: Vitamin D has several physiological functions besides its well-known role in the hemostasis of calcium. There are many contradictory reports about vitamin D deficiency in hypothyroid patients, showing the relation is not conclusive. In this study, we focused on vitamin D–deficient individuals and clarified whether a thyroid dysfunction or calcium imbalance was present. The results are interpreted and discussed according to different vitamin D deficiency criteria. Materials and Methods: Clinical data of a total of 772 people who were referred to the laboratory for their routine care were collected for one year. They had preprescribed tests for T4, TSH, calcium, and vitamin D. Subjects were sorted into vitamin D deficiency, insufficiency, and sufficiency groups based on their vitamin D levels. Mean levels of thyroid hormones, calcium, and age were compared between groups, and their correlations were determined. Results: Among the participants, 74.2% had vitamin D deficiency or insufficiency. No difference in calcium levels was observed between the groups. T4 levels increased significantly, and TSH decreased nonsignificantly with increasing vitamin D levels. However, changes in T4 and TSH levels were within the reference ranges. Vitamin D levels were nonsignificantly correlated with T4 and negatively with TSH. Conclusion: Vitamin D deficiency could not cause thyroid function and serum calcium levels to walk out of the reference ranges. It seems that in our study conditions, vitamin D deficiency does not cause obvious hypothyroidism and hypocalcemia. Part of this discrepancy seems to be related to the current vitamin D reference intervals, which should be revised.